Online Graduate Student Identity and Professional Skills Development - Hurst, Deborah; Cleveland-Innes, Martha; Hawranik, Pamela; Gauvreau, Sarah (Canadian Journal of Higher Education, 2013)
Graduate students are assumed to develop skills in oral and written communication and collegial relationships that are complementary to formal graduate programs. However, it appears only a small number of universities provide such professional development opportunities alongside academic programs, and even fewer do so online. There appears to be an assumption in higher education that students develop professional skills by virtue of learning through required academic tasks and having proximity to other students and faculty. Skeptics of online study raise questions about whether graduate students studying online can participate fully in such graduate communities and access these informal professional skill-building opportunities. It is possible that such activities may have to be designed and delivered for online graduate students. This paper presents preliminary qualitative findings from a project that developed, offered, and evaluated such online opportunities. Findings suggest that while online graduate students can and do develop professional skills while navigating their studies, building relationships, and participating in online learning communities, they are keen to develop such professional skills in a more deliberate way.